Border concatenations: pedagogies, opportunities, sensitive worlds and COVID-19 (Praxis Educativa, 2020)
The work tries to give an account of reflective exercises that have awakened the different interventions that are evident from the appearance of the pandemic and the conditions from which it is made -possible?- to look into the field of education and pedagogy as vital actions. Six reflections as questions are put forward to reconfigure borders and open new contemplations and possible actions: what remains and what changes; fears and how they can paralyze or draw new horizons, the possibility of thinking about this crisis to reignite social solidarity: the borders between normality and exceptionality; the condition of pedagogy in vital terms and as sensitive gestures and what saves us? Thinking about giving an opportunity to education and sustaining the option of vital pedagogies refer us to borders that we are encouraged to cross, as a way of accounting for that vital responsibility that we have as teachers of public institutions in times of “exceptionality”.
Keywords: continuity-discontinuity; social solidarity; vital pedagogies; possible worlds; COVID-19.